1997
DOI: 10.1099/00221287-143-6-1877
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion of benzoic acid in Saccharomyces cerevisiae by an energy-dependent mechanism

Abstract: When grown in the presence of benzoic acid, Saccharomyces cerevisiae was able to extrude [14C]benzoic acid when a pulse of glucose was given to preloaded cells. While octanoic, sorbic, hexanoic, salicylic, butyric and propionic acids were also inducers, ethanol and acetic acid were not. The mechanism of extrusion required energy and prior growth in the presence of the inducers. Diethylstilbestrol, an inhibitor of ATPases, prevented benzoic acid extrusion. Propionic acid was not actively extruded in cells adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
38
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 22 publications
(32 reference statements)
5
38
0
Order By: Relevance
“…Alteration of the plasma membrane composition upon sorbic acid stress in Z. rouxii was described previously (29). In addition, S. cerevisiae and Z. bailii cells adapted to benzoic acid have a reduced permeability to benzoate (33,71). We suggest that in B. subtilis, the observed induction of the fab genes and the bkd operon is a direct response to sorbic acid that will likely alter the membrane composition such that the diffusion rate of the organic molecule over the membrane is lowered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration of the plasma membrane composition upon sorbic acid stress in Z. rouxii was described previously (29). In addition, S. cerevisiae and Z. bailii cells adapted to benzoic acid have a reduced permeability to benzoate (33,71). We suggest that in B. subtilis, the observed induction of the fab genes and the bkd operon is a direct response to sorbic acid that will likely alter the membrane composition such that the diffusion rate of the organic molecule over the membrane is lowered.…”
Section: Discussionmentioning
confidence: 99%
“…These processes, however, may reduce energy resources significantly (8,35,36). Studies with benzoic acid showed that adapted S. cerevisiae and Zygosaccharomyces bailii cells reduce their permeabilities to benzoate (33,71). Changes in fatty acid composition in sorbate-stressed Zygosaccharomyces rouxii cells have been reported (29).…”
mentioning
confidence: 99%
“…Nevertheless, Pdr12 action clearly enhances sorbate, benzoate and acetate resistance (Piper et al, 1998 ;Holyoak et al, 1999). Also it has long been known that acid-adapted S. cerevisiae and Z. bailii can maintain an intracellular versus extracellular distribution of benzoate that is not in equilibrium (Warth, 1977(Warth, , 1988(Warth, , 1989Henriques et al, 1997 ;Piper et al, 1998). This indicates the induction of a system whereby adapted cells can reduce their intracellular weak acid pool.…”
Section: What Is the Pdr12-inducing Signal?mentioning
confidence: 99%
“…Accumulation of radiolabeled acetic acid was determined essentially as described previously for measurements of the uptake of radiolabeled benzoic acid (10,23). Fifty-milliliter mid-exponential-phase cultures, grown at 30°C on pH 4.5 DO or YPD medium, were harvested and resuspended (5 ϫ 10 7 cells ml Ϫ1 ) in 6 ml of medium of the same pH containing 100 mM acetic acid, which was labeled with 25 Ci (15) (Amersham, United Kingdom).…”
mentioning
confidence: 99%